Liver cytosolic 1 antigen-antibody system in type 2 autoimmune hepatitis and hepatitis C virus infection. Issue 5 (May 1995) - Lenzi, M; Manotti, P; Muratori, L; Cataleta, M; Ballardini, G; Cassani, F; Bianchi, F B
Abstract : Within the multiform liver/kidney microsomal (LKM) family, a subgroup of sera that reacts with a liver cytosolic (LC) protein has been isolated and the new antigen-antibody system is called LC1. Unlike LKM antibody type 1 (anti-LKM1), anti-LC1 is said to be unrelated to hepatitis C virus (HCV) infection and has therefore been proposed as a marker of 'true' autoimmune hepatitis type 2. Altogether 100 LKM1 positive sera were tested by immunodiffusion (ID). Twenty five gave a precipitation line with human liver cytosol; 17 of the 25 also reacted with rat liver cytosol. Thirteen of the 25 sera were anti-HCV positive by second generation ELISA: anti-HCV positive patients were significantly older (p < 0.001) and tended to have less active disease. No difference in anti-LC1 titre or ID immunoreactivity was found between anti-LC1/anti-HCV positive and anti-LC1/anti-HCV negative cases. In Western blotting experiments, 14 of 24 ID positive sera recognised a 58 kD protein of the human cytosolic fraction and 11 gave a similar reactivity when tested with human microsomes, suggesting the presence of the LC1 target antigen also in the microsomal preparation. Western blotting reactivity was similar for both anti-HCV positive and negative sera. These data confirm the existence of the LC1 antigen-antibody system that partially overlaps with LKM1, and that it is an additional marker of juvenile autoimmune hepatitis type 2. It does not, however, discriminate between patients with and without HCV infection.